TO EMPTY THE SEA WITH A THIMBLE: READERLY EXPLOITS, DISCOVERIES AND LOSSES - Piotr Nowak (Высшее образование в России, 2016)
From the late forties of 20th century and until 1989, the year which many of my readers in Poland will associate with the end of censure, publishing houses were highly cautious and selective in their production of outstanding works of literature, philosophy and other scholarly works. It appears that we are still trying to compensate for these years of communist dry spell. The avalanche of attention-worthy books keeps growing, bursting into our already well-stocked bookshelves, in direct proportion, it seems, to the growing crisis of literacy and rising inflation of education. Still, to purchase books is not quite the same as to read them. Therefore we may divide contemporary society into two categories based on people's attitude to books. On the one hand, there will be the minority of those who read ceaselessly, even obsessively; on the other - those who never touch books unless planning to make a purchase. This essay examines the consequences of non-reading for culture. The author investigates the phenomenon of non-reading in its broadest sense, discussing different attitudes to this problem as well as diverse varieties of non-reading.